Levantamento de raças do agente causador do míldio da alface no Estado de São Paulo em 2012 e 2013 - de Nunes, Renata Castro [UNESP]; Castoldi, Renata [UNESP]; Gomes, Rafaelle Fazzi [UNESP]; Tobar-Tosse, Dora Enith [UNESP]; Braz, Leila Trevisan [UNESP] (FapUNIFESP (SciELO), 2016)
Lettuce is, among leafy vegetables, the most economically important one to Brazil. In the winter, at low temperatures and under leaf wetness, downy mildew of lettuce, a disease caused by the etiologic agent Bremia lactucae, occurs in almost all regions where this vegetable is grown and is considered one of the most severe foliar diseases for the culture. The aim of this study was to identify the races of B. lactucae in 2012 and 2013 that occurred in the main producing regions of São Paulo State, such as: Ribeirão Preto, Jaboticabal, Pirangi, Catanduva, São José do Rio Preto, Atibaia, Salesópolis, Biritiba Mirim, Mogi das Cruzes, Campinas, Itapira, Mogi Mirim, Cândido Mota, Presidente Prudente, Echaporã, Assis, Marilia, Botucatu and Bauru. During the months of July/August 2012 and 2013, we collected samples of lettuce leaves showing symptoms of downy mildew, and in each collected sample the pathogen structures referred to an isolate. The sporangia were multiplied on the susceptible cultivar Solaris, with subsequent inoculation in differential cultivars, performing evaluations on the 12th day from the appearance of the first sporulation in the susceptible cultivar ‘Green Tower’ (Dm-0), according to the code “Sextet”. In 2012, two new codes were determined, identifying two new races, SPBl:10 (63/31/02/00) and SPBl:11 (63/63/18/00). In 2013, a new codification was determined (63/31/18/00), to which the name SPBl:12 was proposed. The genes Dm-14 and Dm-15 and the resistance factors FR-17, FR-18, FR-36, FR-37 and FR-38 confer resistance to these new races that were identified. It is recommended, therefore, in breeding programs of lettuce, the use of factors FR-17, FR-18 and FR-38 as sources of resistance for new cultivars developed in the state of São Paulo, because they confer resistance to all 12 already identified races.
Survey of races of the causal agent of downy mildew of lettuce in the state of São Paulo in 2012 and 2013
Keywords: Bremia lactucae; Genes Dm; Lactuca sativa L; Resistance of plants to disease